2013
DOI: 10.1016/j.physleta.2013.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Ranking spreaders by decomposing complex networks

Abstract: Ranking the nodes' ability of spreading in networks is crucial for designing efficient strategies to hinder spreading in the case of diseases or accelerate spreading in the case of information dissemination. In the well-known k-shell method, nodes are ranked only according to the links between the remaining nodes (residual links) while the links connecting to the removed nodes (exhausted links) are entirely ignored. In this Letter, we propose a mixed degree decomposition (MDD) procedure in which both the resid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
184
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(186 citation statements)
references
References 50 publications
2
184
0
Order By: Relevance
“…Also, Chen et al [27] introduced a so-called ClusterRank method, which takes the influence of neighbor nodes and clustering coefficient into consideration. Zeng and Zhang [28] improved the established k-shell method by rethinking the significant connections between nodes and removed nodes and proposed a mixed degree decomposition method. Pei et al [29] confirmed that the most influential actors are situated in the k-core across disparate social platforms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, Chen et al [27] introduced a so-called ClusterRank method, which takes the influence of neighbor nodes and clustering coefficient into consideration. Zeng and Zhang [28] improved the established k-shell method by rethinking the significant connections between nodes and removed nodes and proposed a mixed degree decomposition method. Pei et al [29] confirmed that the most influential actors are situated in the k-core across disparate social platforms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, many scholars have extended and improved K-core. For example, Zeng et al [21] considered the information of the Ks degree of removed nodes after Ks decomposition, and they proposed the mixed degree decomposition method (MMD). Garas et al [22] developed Ks decomposition for weighted networks.…”
Section: Introductionmentioning
confidence: 99%
“…It was in 2013 that Zeng and Zhang proposed a modification of k-shell method called the mixed degree decomposition (MDD) [8]. The method is described as follows.…”
Section: Mixed Degree Decomposition Methodsmentioning
confidence: 99%
“…Importance of nodes in the transmission of information is a matter of great concern in literature of information diffusion in networks [8][9][10]. As mentioned in the previous paragraph, some nodes that have large number of connections are highly important in the sense that any piece of information in their hands may spread faster than that in the hands of others.…”
Section: Introductionmentioning
confidence: 99%